'A really good teaching strategy': Secondary students with vision impairment voice their experiences of inclusive teacher pedagogy. (May 2014) - Whitburn, Ben
The inclusion of students with vision impairment (VI) into regular classes is typically made possible via a raft of technical accommodations and special educational support. This article reports key findings of a small-scale qualitative Australian study conducted with a group of secondary school students with VI about teachers' practices that increased their access and autonomy. Participants reported that a combination of (1) using appropriate communication modes, (2) making accessible resources available to students in a timely manner, (3) being able to 'think outside the box' about the provision of access to diagrammatic study material, and (4) being approachable outside of scheduled lessons for individual consultations increased their inclusion in the school. Raw data are presented to illustrate the value of these practices to the students. This article concludes with a discussion of the potential of students' views to the facilitation of inclusive practices, and the broader implication of this to the teaching profession.